Descriptive Memoir of Ministry of Defence, April 1956 - Planning Commission (Planning Commission, 1956)
The Ministry of Defence is responsible for all matters relating to the defence of the country, a subject falling-entirely in the Central sphere. the statutory functions briefly relate to the following important headings:- (a) Defence of India and every part thereof including preparation for defence and all such acts as may be conducive in times of war to its prosecution and after its termination to effective demobilisation including Marine Surveys and dangers to Navigation. (b) Military, Naval and Air Forces; and other armed forces of the Union including National Cadets Corps, the Territorial Army and the National Volunteer Force.
Organisation and Methods Division Cabinet Secretariat